Controllability of block diagonal systems and applications. (29th March 2011) - Larez, Hanzel; Leiva, Hugo; Uzcategui, Jahnett
In this paper we present necessary a sufficient conditions for the exact and approximate controllability of Block-Diagonal Control Systems representing a broad class of linear evolution equations in Hilbert spaces. We apply these results to the controlled nD wave equation, heat equation and thermoelastic plate equation.